Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemampuan Berfikir Kreatif - ahmad nasobandi (Neolectura, 2022)
This research is motivated by the low level of students' creative thinking skills. during this time the teacher only used discussion and lecture learning methods. The purpose of this study was to determine the application of the project based learning model to the creative thinking skills. The research method used in this research is a quasi-experimental research. This research was conducted in class VII.A and VII.B. data collection techniques namely by observation, documentation, and objective tests, namely tests given at the end of learning. After the objective data is collected, the processing is carried out with a validity test, a reliability test, a level of difficulty test and a differentiating power test. Based on the results of the normality and homogeneity tests, namely 97.67667, the test results from the two groups were normal and homogeneous. So to test the hypothesis using the t-test two samples are not correlated.